Enhancing Vietnamese criminal law on personal data protection in cyberspace to foster cooperation with the European Union - Hong Nguyen Thi Anh; Thao Tran Thanh (TalTech Journal of European Studies)
Protecting personal data in cyberspace is an issue of significant concern to many countries around the world, including Vietnam. The invasion of personal data in cyberspace is currently common in Vietnam; however, these dangerous acts have not been dealt with effectively because of gaps in Vietnamese law regarding personal data in general and Vietnamese criminal law concerning these crimes in particular. By applying analytical-logical and comparative methods, this article aims to refine the provisions of Vietnamese criminal law on personal data protection in cyberspace. Starting by analyzing the provisions related to acts of personal data violation in cyberspace according to Vietnamese law and the shortcomings in their practical application, this article looks at European Union laws, specifically the General Data Protection Regulation and the Budapest Convention on Cybercrime. It then proposes some recommendations for improving Vietnamese criminal law regarding personal data violations in cyberspace to ensure compatibility between Vietnamese law and EU law.